Pengaruh Teman Sebaya Terhadap Sosial Emosional Anak Usia Dini Di Desa Pal 30, Kecamatan Lais, Kabupaten Bengkulu Utara - Septa Lestari, Dwi; Ediansyah, Ediansyah; Budrianto, Budrianto (UIN Fatmawati Sukarno Bengkulu, 2025)
This study uses a quantitative approach with an ex post facto method. The researcher used the entire population as the sample, totaling 30 respondents. The sampling technique used was non-probability sampling with a total sampling technique. Data was collected through a questionnaire consisting of 25 statements for the peer variable and 25 statements for the socio-emotional variable, filled out by 30 respondents. Data analysis was performed with validity and reliability tests, which showed that all instruments were valid and reliable, with a Cronbach Alpha value of 0.793 for the peer variable and 0.786 for the socio-emotional variable. The results of this study indicate that there is a significant influence of peers on the socio-emotional development of children in Desa Pal 30, Lais Subdistrict, North Bengkulu Regency. Based on the regression analysis, it was found that the relationship between peers as the independent variable and socio-emotional development as the dependent variable is positive. The coefficient table shows that, in the significance column, the significance value is 0.000 < 0.05, so it can be concluded that the peer variable (X) has an effect on the socio-emotional variable (Y). The size of the influence in the obtained regression equation is Y = 31.918 + 0.566X, with a coefficient of determination (R Square) of 0.404, which indicates that peers influence 40.4% of the socio-emotional development of children, and it is a positive influence. Overall, the results of this study indicate that peers have an impact on the socio-emotional development of early childhood. Therefore, it can be concluded that H1 is accepted and H0 is rejected